Effectiveness of Use of Islamic Integrated Mathematics E-Modules To Improve Mathematical Problem Solving Capability - Hanif Khairi; Dony Permana; Yerizon; I Made Arnawa (Jurnal Penelitian Pendidikan IPA, 2023)
The unavailability of teaching materials that can support mathematical problem-solving abilities and are integrated with Islamic teaching values makes it difficult for SMP IT educators to hone students' mathematical problem-solving abilities and difficulties in instilling Islamic values in students. One solution that educators can use in learning is to use e-modules. E-module is a teaching material that has the characteristics of independent learning principles. This research aims to see the effectiveness of using mathematics e-modules that are integrated with Islamic values in facilitating students' mathematical problem-solving abilities. This type of research is pre-experimental research and the research design is one group pre-test-post test design. The sampling method is purposive sampling, where one class is taken directly from the population as a research sample. The subjects of this research were 24 students in class VIII.1 at SMP IT Qurrata A'yun Batusangkar. The effectiveness of the mathematics e-module can be seen from the comparison of the results of the pre-test and post-test of students' mathematical problem-solving abilities. The final results of the student's mathematical problem-solving ability test obtained were 57% of the total maximum score, while the results of the student's initial mathematical problem-solving ability test were only 22% of the maximum score. Because 57%>22%, these results indicate that the use of Islamic integrated mathematics e-modules is effective in facilitating students' mathematical problem-solving abilities.